Pengembangan Aplikasi Smart Transportation Berbasis Real-Time Tracking dan Pembayaran Digital untuk Bus Listrik Menggunakan Metode Research and Development (R&D) - Dolly Brams Matondang; Susilo Immanuel Situmorang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The development of digital technology has encouraged innovation in public transportation services through the concept of smart transportation. However, electric bus services still face limitations in providing real-time bus location information and have not yet integrated digital payment systems within a single platform. These conditions make it difficult for users to obtain arrival time information and perform payment transactions efficiently. This study aims to develop a mobile-based smart transportation application that integrates real-time tracking, Estimated Time of Arrival (ETA), route and bus stop information, and digital payment services through mobile banking, e-wallets, and QR code. The Research and Development (R&D) method was applied because it supports a systematic system development process starting from needs analysis, system design, prototype development, and usability testing. The contribution of this research lies in the development of an integrated application to facilitate users in accessing electric bus services more effectively and efficiently, considering that there is currently no application that completely integrates these features into a single platform. Usability testing using the System Usability Scale (SUS) method involving 30 respondents produced an average score of 87.3, which falls into the Excellent, Grade A, and Acceptable categories. These results indicate that the application has a very good level of usability and is feasible for further development.